2006
DOI: 10.1111/j.1365-3032.2006.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical information from the fungus Amylostereum areolatum and host‐foraging behaviour in the parasitoid Ibalia leucospoides

Abstract: Parasitoids locate hosts using reliable and predictable cues such as smells derived from host plants or from the hosts themselves. For host species that live with mutualistic organisms, such as several wood boring insects, cues derived from the symbionts are likely to be exploited by specific parasitoids. Through a set of bioassays, the behaviour of the parasitoid Ibalia leucospoides Hochenwarth (Hymenoptera: Ibaliidae) is studied in response to the fungus Amylostereum areolatum Boidin (Basidiomycotina: Cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…An alternative explanation is that the preservative components of the diet affected the microorganisms associated with H. hampei, and therefore the dust/frass volatiles. Some studies have shown that the production of volatile infochemicals depends on the presence of microorganisms and not on enzymes arising from the plant or the herbivore (Godfray 1994;Martínez et al 2006;Steiner et al 2007). Whether some of the microorganisms associated with H. hampei are involved in the production of volatile kairomone remains to be investigated.…”
Section: Discussionmentioning
confidence: 97%
“…An alternative explanation is that the preservative components of the diet affected the microorganisms associated with H. hampei, and therefore the dust/frass volatiles. Some studies have shown that the production of volatile infochemicals depends on the presence of microorganisms and not on enzymes arising from the plant or the herbivore (Godfray 1994;Martínez et al 2006;Steiner et al 2007). Whether some of the microorganisms associated with H. hampei are involved in the production of volatile kairomone remains to be investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Females of I. leucospoides oviposit inside the eggs and 1st instar larvae of woodwasps, which are burrowed deep inside the xylem tissue of pines. It is well known that I. leucospoides uses chemical cues, derived from a fungal symbiont of S. noctilio, to locate host eggs and larvae within a tree (Madden 1968;Spradbery 1974;Martínez et al 2006). Adults emerge, usually a year later, with a high number of mature eggs (~500, Fischbein 2011).…”
Section: Biology Of Ibalia Leucospoidesmentioning
confidence: 99%
“…The mycelium used in the bioassays was excised from the culture dishes into 170 mm discs. The fungus culture was used as a chemical signal of possible oviposition sites to I. leucospoides (Martínez et al 2006). …”
Section: Parasitoid Rearing and Fungus Culturingmentioning
confidence: 99%
See 1 more Smart Citation
“…A great variety of environmental cues, such as chemical, visual and physical cues, are used by parasitoids as sources of information for both locating and assessing host patches (Vet & Dicke, 1992; Godfray, 1994). These cues of various natures can act as indicators of host presence, host species (Thiel & Hoffmeister, 2006) and host density (Waage, 1979; Li et al , 1997; Shaltiel & Ayal, 1998; Wang & Keller, 2004; Tentelier et al , 2005; Martínez et al , 2006, Corley et al , 2010), as well as of the presence of competitors in the current patch (Janssen et al , 1995a,b; Bernstein & Driessen, 1996; Castelo et al , 2003). The use of such information is expected to reduce uncertainty and therefore improve foraging success.…”
Section: Introductionmentioning
confidence: 99%